The Influence of Leadership and Work Discipline on Employee Performance Mediated By The Organization's Commitment To PT Nusantara Power Engineering Medan - Marwazi; Mesra B.; Muhammad Isa Indrawan (International Journal of Management, Economic and Accounting, 2023)
This study aims to determine the Influence of Leadership and Work Discipline on Employee Performance Mediated by Organizational Commitment at PT Nusantara Power Engineering Medan. The research method used in the study is quantitative method, in this study there are one 2 independent variables, 1 intervening variable, and 1 dependent variable. The population in this study was 47 yarn employees of PT Nusantara Power Engineering Medan. The sampling technique in this study is saturated samples. The data withdrawal technique used was a questionnaire with Likert scale. The data analysis technique to answer this research hypothesis is the Structural Equation Model (SEM). The results showed that leadership variables had no effect on employee performance, leadership variables did not affect organizational commitment, work discipline variables had an effect on employee performance, work discipline variables had no effect on organizational commitment, and organizational commitment variables had an effect on employee performance.